1989
DOI: 10.1056/nejm198903023200905
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Drug Response

Abstract: To determine whether the pharmacokinetics and pharmacodynamics of beta-blockade differ among racial groups, we gave 10 men of Chinese descent and 10 American white men 10, 20, 40, and 80 mg of propranolol every eight hours; the dosages were given in random order, and each dose was given for one day. The degree of beta-blockade was measured as the reduction in the heart rate and blood pressure in the supine and upright positions and during treadmill exercise testing. The Chinese subjects had at least a twofold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…It was reported that Chinese are more sensitive than Caucasians to the effects of the beta-blocker propranolol on the pulse rate and BP [18]. Because Asians appear to be more sensitive to beta-blockers, renal denervation may be more effective for Asian patients with R-HT, and patients who have tachycardia like our No.…”
Section: Investigating Candidates For Renal Denervationmentioning
confidence: 50%
“…It was reported that Chinese are more sensitive than Caucasians to the effects of the beta-blocker propranolol on the pulse rate and BP [18]. Because Asians appear to be more sensitive to beta-blockers, renal denervation may be more effective for Asian patients with R-HT, and patients who have tachycardia like our No.…”
Section: Investigating Candidates For Renal Denervationmentioning
confidence: 50%
“…1,2 Large pharmacodynamic variability has limited the usefulness of plasma drug concentration monitoring for individualizing therapy. Variation in drug response arising from biological diversity between individuals has been associated with covariates such as age, [3][4][5][6] genetics, [7][8][9][10] or disease states. [11][12][13][14][15][16][17] Since knowledge of important covariates can be used to refine individualized therapy, the identification of clinically relevant pharmacodynamic covariates is a primary goal of many pharmacodynamic investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was recently demonstrated in Caucasians (Germans) that the clearance of (S)-propafenone interindividual variability in drug action [1]. Recently racial differences between Caucasian and Chinese subjects both in was significantly lower during treatment with racemic propafenone compared with when the (S)-enantiomer was the pharmacokinetics and pharmacodynamics of morphine [2], atropine [3] and propranolol [4] have been reported.…”
mentioning
confidence: 99%